PSYCHOLOGICAL WELL BEING MAHASISWA DALAM MENJALANI KULIAH DARING UNTUK MENCEGAH PENYEBARAN VIRUS CORONA (Studi terhadap Mahasiswa Bimbingan Konseling Islam UIN Imam Bonjol Padang) - Dyla Fajhriani. N Dyla; Afnibar Afni; Aulia Rahmi Rahmi (Universitas Islam Negeri Imam Bonjol Padang, 2020)
ABSTRACTPsychological well being is one of the psychological conditions experienced by students that affects their learning, especially when outbreaks of new corona viruses (COVID 19). The purpose of this study was to determine the Psychological well being students in undergoing online lectures (in networks) to prevent the spread of corona virus. This study uses a qualitative research method, which is descriptive by using interviews and documentation analysis of WhatsApp Group (WAG) conversations, to students majoring in Islamic Counseling, as many as 30 students of Islamic Counseling. The results revealed that students were more comfortable in attending face-to-face lectures than undergoing online lectures.